Att stödja tvärvetenskapliga doktoranders frigörelse från disciplinära föreställningar - Brandstedt, Eric (Högre utbildning, 2022)
Ambitious ideals about interdisciplinarity are notoriously difficult to put into practice, partly because they are counteracted by how many universities are organised. This is a problem for doctoral students in interdisciplinary projects as well as for their supervisors. Interdisciplinary doctoral students, like all doctoral students, have a research subject in which they are expected to develop into independent researchers, but also an expectation that they will broaden and integrate perspectives from other subjects. This leads to a difficult challenge for both the doctoral student and its supervisor: how should the time be enough? It is difficult to combine reasonable demands and expectations on doctoral students’ independence development with achieving ambitious interdisciplinary ideals. How can this be handled from the perspective of the supervisor who has a more monodisciplinary background than the one the doctoral student is expected to get? How can this supervisor support the doctoral student’s development into an independent interdisciplinary researcher? This article focuses on monodisciplinary preconceptions that supervisors of interdisciplinary doctoral students convey and how they can limit the doctoral students’ opportunities to become independent interdisciplinary researchers. An ideal of a kind of emancipation from certain monodisciplinary ideas is formulated.
Original title: Att stödja tvärvetenskapliga doktoranders frigörelse från disciplinära föreställningar
Keywords: självständighetsutveckling; frigörelseprocess; tvärvetenskap; socialisering; Independence development; emancipation; interdisciplinarity; socialisation